Impacts of irrigation efficiency on water-dependent sectors are heavily controlled by region-specific institutions and infrastructures. (15th December 2021) - Malek, Keyvan; Adam, Jennifer; Yoder, Jonathan; Givens, Jennifer; Stockle, Claudio; Brady, Michael; Karimi, Tina; Rajagopalan, Kirti; Liu, Mingliang; Reed, Patrick
Abstract: Farmers' investment in more efficient irrigation systems represents a primary adaptation strategy when confronting climate change. However, the regional benefits of these investments and their influence on the conflicting demands among different water dependent stakeholders for intensely irrigated regions remains an open question. Using the Pacific Northwest of the United States as an illustrative region of focus, we show that higher irrigation efficiency has diverse effects across stakeholders that are contingent on many local climatic, institutional and infrastructural factors such as the availability of water storage, the location of hydropower generators, and water rights. These complexities limit simple abstractions of irrigation efficiency as broader policy challenge and are central to its inclusion within the class of "wicked problems". Additionally, we argue that the widely used rebound effect concept, which implicitly discourages irrigation efficiency supporting policies, should not be assumed to fully capture the nuances of the complex suite of regional impacts that emerge from irrigation efficiency investments. Consequently, the evaluation of irrigation efficiency investments requires a broader framing across a diversity of perspectives. policies and actions that are pluralistic, context-specific, and closely engage various groups of stakeholders in the policymaking process. Highlights: Climate change impacts on supply and demand will interact with IE effects. Higher IE improves the overall performance of agricultural systems during droughts. IE can generate complex and path-dependent implications for various stakeholders. Efficiency policymakers should consider region-specific institutional contexts. The Rebound Effect concept can oversimplify IE impacts and lead to biased policies.